High resolution modelling of the Bay of Algeciras (Strait of Gibraltar) with application to biogeochemical processes. - Naranjo-Rosa, Cristina Belén; García-Lafuente, Jesús; Sánchez-Garrido, José Carlos; Sammartino, Simone (My University, 2017)
The Western Alborán Sea is an eutrophic sub-basin within the Mediterranean Sea, typically oligotrophic. It is especially eutrophic in the north-western coast, where we found the Algeciras Bay, a semi-enclosed inlet of about 9x11 km, opened in its south margin. As part of the Strait of Gibraltar system, it has a high energetic dynamics and presents flushing times of a few days. The analysis of Chl images from satellite in the area Strait of Gibraltar-Western Alborán Sea, reveals that primary productivity of the Alborán Sea follows an annual cycle with maximum chlorophyll concentrations in winter and minimum in summer, which has been already addressed by several authors. On the contrary, surface Chl in the Algeciras Bay shows several blooms both, in spring and autumn. Despite this apparent disjunction between the two close systems, most of the time the Bay and the north-western Alboran Sea belong to the same upwelling system, but satellite images reveals that occasionally the Bay behaves as a source of primary productivity for the north-western Alborán Sea. This work presents the preliminary results of the coupling of a biogeochemical (NPZD) and a hydrodynamic model, both broadly validated with several sources of observations (MODIS-aqua satellite and moorings). Main results show that the Bay of Algeciras has great primary productivity, and despite being linked to the upwelling system of the north-western Alborán Sea, occasionally behaves as a separate system, with high blooms occurring within the Bay, but low chlorophyll in the nearby basin. When the latter occurs, it results in the export of primary productivity from the Bay to the Alborán Sea
Keywords: Biogeoquímica - Congresos; Algeciras Bay; Biogeochemical; Gibraltar